An asynchronous Mesozoic marine revolution: the Cenozoic intensification of predation on echinoids. Issue 1947 (31st March 2021) - Petsios, Elizabeth; Portell, Roger W.; Farrar, Lyndsey; Tennakoon, Shamindri; Grun, Tobias B.; Kowalewski, Michal; Tyler, Carrie L.
Abstract : Predation traces found on fossilized prey remains can be used to quantify the evolutionary history of biotic interactions. Fossil mollusc shells bearing these types of traces provided key evidence for the rise of predation during the Mesozoic marine revolution (MMR), an event thought to have reorganized global marine ecosystems. However, predation pressure on prey groups other than molluscs has not been explored adequately. Consequently, the ubiquity, tempo and synchronicity of the MMR cannot be thoroughly assessed. Here, we expand the evolutionary record of biotic interactions by compiling and analysing a new comprehensively collected database on drilling predation in Meso-Cenozoic echinoids. Trends in drilling frequency reveal an Eocene rise in drilling predation that postdated echinoid infaunalization and the rise in mollusc-targeted drilling (an iconic MMR event) by approximately 100 Myr. The temporal lag between echinoid infaunalization and the rise in drilling frequencies suggests that the Eocene upsurge in predation did not elicit a coevolutionary or escalatory response. This is consistent with rarity of fossil samples that record high frequency of drilling predation and scarcity of fossil prey recording failed predation events. These results suggest that predation intensification associated with the MMR was asynchronous across marine invertebrate taxa and represented a long and complex process that consisted of multiple uncoordinated steps probably with variable coevolutionary responses.